2015
DOI: 10.1002/hep.27966
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of strategies for testing current hepatitis C virus infection

Abstract: Six strategies for identifying hepatitis C virus (HCV) viremia, involving testing for HCV antibody (HCVAb) followed by a nucleic acid test (NAT) for HCV RNA when the antibody test is positive, are compared. Decision analysis was used to determine mean relative cost per person tested and outcomes of HCV viremia detection. Parameters included proportions of test population with HCVAb and viremia plus specificity, sensitivity, and cost of individual tests. For testing a population with an HCVAb seroprevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 24 publications
(45 reference statements)
0
27
0
Order By: Relevance
“…Reflex RNA testing for HCV antibody positive samples has been proposed as a strategy to further bridge this gap in the care cascade, and is currently being piloted in BC. Reflex genotyping has been shown to be cost effective and improve progression to genotyping in other settings.…”
Section: Discussionmentioning
confidence: 99%
“…Reflex RNA testing for HCV antibody positive samples has been proposed as a strategy to further bridge this gap in the care cascade, and is currently being piloted in BC. Reflex genotyping has been shown to be cost effective and improve progression to genotyping in other settings.…”
Section: Discussionmentioning
confidence: 99%
“…There are statistical challenges with determining a "number needed to screen" to detect a relatively rare disease in lower-risk settings; therefore, providers and program directors are encouraged to consult their state or local health departments or CDC to determine a reasonable estimate of baseline prevalence in their setting or a methodology for determining how many persons they need to screen before confidently establishing that the prevalence is <0.1%. As a general guide: as HCV RNA prevalence is predicated on first testing for anti-HCV, and according to the most current serologic data in the United States, approximately 59% of anti-HCV positive persons are HCV RNA positive (2), an estimated 507 randomly selected patients in a setting of any size would need to be tested using any of the available anti-HCV tests (94) to detect an anti-HCV prevalence positivity of ≤0.17%, corresponding to an expected HCV RNA positivity prevalence of 0.1% with 95% confidence and 5% tolerance (95) (https://epitools.ausvet.com.au).…”
Section: Determining Prevalencementioning
confidence: 99%
“…Four studies assessed different types of test or screening programs without including the treatment options available for the HCV and the health improvement associated to virus eradication . These studies’ characteristics are reported in the Table S1, but they are not described in details in this review.…”
Section: Resultsmentioning
confidence: 99%